Vida política en la Argentina del Siglo XIX Armas, votos y voces - SABATO, Hilda comp. (FONDO DE CULTURA ECONOMICA, 2003)
Otro descriptor: SUFRAGIO; SANTA FE; HISTORIOGRAFIA.Otros autores: ROLDAN, Darío; GOLDMAN, Noemí; TERNAVASIO, Marcela; MYERS, Jorge; CHAMOSA, Oscar; MACIAS, Flavia; BERTONI, Lilia Ana; DI MEGLIO, Gabriel; GONZALEZ BERNALDO, Pilar; BRAGONI, Beatriz; PAZ, Gustavo L.; BRAVO, María Celia; BONAUDO, Marta; ALONSO, Paula; HORA, Roy